2018
DOI: 10.1002/jgf2.229
|View full text |Cite
|
Sign up to set email alerts
|

Quality of primary care provided in community clinics in Japan

Abstract: Background Quality indicators (QIs) for primary care are used worldwide. To date, however, the use of QIs to assess the quality of primary care in Japan has not been reported besides diabetes care. Here, we used QIs to evaluate the quality of primary care services provided by local clinics in Japan. Methods Four primary care clinics participated in the retrospective medical chart review in 2015. To assess primary care quality, we used 18 process‐oriented QIs from the Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The use of PCAT is widespread in health services in Brazil, in the states of São Paulo, Rio de Janeiro and especially in Rio Grande do Sul. In agreement with Ozaki et al (2019), 1 when they mention that primary care plays an “increasingly important role in the healthcare system ,” we propose a leap beyond. Why not outline a national policy for primary care assessment including users’ perspective?…”
Section: The Use Of Pcat‐brazil and The National Health Survey (Pns‐2supporting
confidence: 89%
See 1 more Smart Citation
“…The use of PCAT is widespread in health services in Brazil, in the states of São Paulo, Rio de Janeiro and especially in Rio Grande do Sul. In agreement with Ozaki et al (2019), 1 when they mention that primary care plays an “increasingly important role in the healthcare system ,” we propose a leap beyond. Why not outline a national policy for primary care assessment including users’ perspective?…”
Section: The Use Of Pcat‐brazil and The National Health Survey (Pns‐2supporting
confidence: 89%
“…Ozaki et al (2019) 1 had evaluated the quality of primary care throughout small facilities using quality indicators (QIs) collected in electronic medical records (EMR) system. They selected 18 QIs based on a comprehensive framework after a modified Delphi method validated by an expert panel members.…”
Section: The Importance Of Patients’ Experience In Assessing the Qualmentioning
confidence: 99%
“…After the initial review, we identified 9 articles, 2 were excluded because they did not contain data on metrics limited to Japan and one was excluded because it involved an intervention. In total, 6 studies encompassing 10 cohorts were included in the final analysis [15][16][17][18][19][20][21][22]. (Fig.…”
Section: Literature Searchmentioning
confidence: 99%
“…One study used data derived from national health insurance claim data among the elderly [15] and two studies used data from health insurance claims data managed by the Japan Medical Data Center (JMDC) Claims Database [16,18]. One study analyzed the National Database of health insurance claims [19] and another study used medical claims and medical records [20].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We thank the authors of the Letter to the Editor 1 for their interest in our article, "Quality of primary care provided in community clinics in Japan" 2 We completely agree with them that patientcenteredness measured by patients' experience is one of the important elements of quality of primary care, along with equitable, timely, safe, effective, and efficient care 3 We also agree with the authors' suggestion that Japanese healthcare policy should implement patients' experience as Brazilian Federal Government do.…”
mentioning
confidence: 99%